Моделирование нестационарных явлений в тлеющем разряде атмосферного давления; Физика плазмы; Т. 42, № 6 - Королев Ю. Д. Юрий Дмитриевич; Франц О. Б. Олег Борисович; Нехорошев В. О. Виталий Олегович; Суслов А. И. Андрей Иванович; Шемякин И. А. Илья Александрович; Болотов А. В. Александр Владимирович (Низкотемпературная плазма, 2016)
Заглавие с экрана